Multifocal Supra and Infratentorial Medulloblastoma in an Adult: Histologic, Immunohistochemical, and Molecular Evaluation of a Rare Case and Review of the Literature - Saad, Ali G; Balik, Vladimir; Parvez, Aatif; El Jamal, Siraj M (Applied immunohistochemistry & molecular morphology, 2017)
Multifocal medulloblastomas (MMBs) in adults are exceedingly rare with only 5 reported cases to date. Medulloblastoma in adult differ from its childhood counterpart by being more often lateral in location, desmoplastic in morphology, and better in clinical prognosis. Little is known, however, about the characteristic features of MMB. This is particularly true for their molecular profiles. To date, molecular characteristics of multifocal medulloblastoma have been reported only once. Here, we present the second case of multifocal medulloblastoma along with its detailed morphology, imaging features, and molecular profiles with a critical review of the literature. We believe that MMB should be reported in detail to better understand their behavior, characterize their molecular profiles, and establish therapeutic protocols.
Keywords: Medulloblastoma; meduloblastom; stanovení celkové genové exprese; infratentoriální nádory; Gene Expression Profiling; Humans; lidé; Infratentorial Neoplasms